2012
DOI: 10.1371/journal.pone.0050074
|View full text |Cite
|
Sign up to set email alerts
|

Weak Compliance Undermines the Success of No-Take Zones in a Large Government-Controlled Marine Protected Area

Abstract: The effectiveness of marine protected areas depends largely on whether people comply with the rules. We quantified temporal changes in benthic composition, reef fish biomass, and fishing effort among marine park zones (including no-take areas) to assess levels of compliance following the 2005 rezoning of the government-controlled Karimunjawa National Park (KNP), Indonesia. Four years after the rezoning awareness of fishing regulations was high amongst local fishers, ranging from 79.5±7.9 (SE) % for spatial res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 54 publications
3
74
1
1
Order By: Relevance
“…When this prerequisite is not met, the MPA effects are substantially reduced or negligible (e.g. Montefalcone et al, 2009;Campbell et al, 2012;Guidetti et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When this prerequisite is not met, the MPA effects are substantially reduced or negligible (e.g. Montefalcone et al, 2009;Campbell et al, 2012;Guidetti et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These factors can prove to be more crucial for determining the success of an MPA than design factors, e.g. the size of the MPA (Pollnac et al, 2010;Daw et al, 2011;Campbell et al, 2012;Ferreira et al, 2015). In the Mediterranean Sea, there are few cases where stakeholders have been actively involved in MPA planning since the onset of the initiative.…”
Section: Introductionmentioning
confidence: 99%
“…In an age-structured model of Black Rockfish, Sethi and Hilborn (2008) found that high rates of poaching negated the biological and fishery benefits of implementing reserves. High rates of noncompliance in reserves have been found to limit recovery of fish communities empirically as well (Campbell et al 2012;Edgar et al 2014;McClanahan et al 2009;McCook et al 2010;Pollnac et al 2010). In an Indonesian marine reserve, Campbell et al (2012) found that low compliance with no-take zones resulted in decreases in fish biomass in all reserve zones despite an observed recovery in coral cover.…”
Section: Discussionmentioning
confidence: 99%
“…High rates of noncompliance in reserves have been found to limit recovery of fish communities empirically as well (Campbell et al 2012;Edgar et al 2014;McClanahan et al 2009;McCook et al 2010;Pollnac et al 2010). In an Indonesian marine reserve, Campbell et al (2012) found that low compliance with no-take zones resulted in decreases in fish biomass in all reserve zones despite an observed recovery in coral cover. In the Great Barrier Reef, McCook et al (2010) found that no-entry zones had a higher abundance of coral trout than no-take and fishing zones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation